2014
DOI: 10.1002/jsfa.6896
|View full text |Cite
|
Sign up to set email alerts
|

5‐Caffeoylquinic acid decreases diet‐induced obesity in rats by modulating PPARα and LXRα transcription

Abstract: 5-CQA may improve lipid metabolism disorders by altering the expression of PPARα and LXRα, which are involved in multiple intracellular signalling pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
64
2
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(79 citation statements)
references
References 53 publications
9
64
2
4
Order By: Relevance
“…This was similar to the results of our group 23 and those of Cho et al 13 who found that CGA improved the body weight, lipid metabolism, and obesity- related hormone levels in obese mice. However, 5-CQA-treated rats showed a significant improvement in these levels.…”
Section: Discussionsupporting
confidence: 92%
“…This was similar to the results of our group 23 and those of Cho et al 13 who found that CGA improved the body weight, lipid metabolism, and obesity- related hormone levels in obese mice. However, 5-CQA-treated rats showed a significant improvement in these levels.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, CGA was shown to decrease cholesterol via LXR (Huang et al . ). In the present study, no differences were observed in whole fish fat (data not shown) and PPARα expression levels in pyloric caeca or liver were not affected by dietary means.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, CGAs contribute to prevent various diseases associated with oxidative stress, as well as cancer, aging, and cardiovascular and neurodegenerative diseases; besides, these substances have promising effects in modulating lipid and glucose metabolism [12][13][14][15]. On the other hand, quantity of CGAs is inversely associated with quality of a coffee cup.…”
Section: Introductionmentioning
confidence: 99%